Is having low motivation the same as not having high motivation? Comparing the CSAS-R and the SAAS-R. (2nd January 2016) - McCoach, Betsy; Newton, Sarah D.; Siegle, Del; Baslanti, Ugur; Picho, Katherine
Abstract : The purpose of the current study was to examine the relationships among the Challenges to Scholastic Achievement Scale-Revised (CSAS-R) and The School Attitude Assessment Survey-Revised (SAAS-R) items and factors to determine whether the negative scales on the CSAS-R seemed to be measuring the same constructs as those that are measured on the SAAS-R. All SAAS-R items are positively worded, and all subscales are designed to measure positive manifestations of the constructs. The CSAS-R is a complementary instrument to the SAAS-R. All items represent negative manifestations of attitudes, cognitions, or behaviors. For this study, we focused on the four constructs from the SAAS-R and the CSAS that are directly comparable and complementary: positive and negative academic self-perceptions, positive and negative attitudes toward teachers and classes, high and low goal valuation, and regulated and unregulated study behavior. This comparison of CSAS-R and SAAS-R examined alternative conceptions of the dimensionality of the positive items (from the SAAS-R) and the negative items (from the CSAS-R) in an effort to better understand whether agreeing to statements about negative behaviors or attitudes seemed to represent the polar opposite of disagreeing to statements about positive behaviors or attitudes.